Left-behind adolescents' hopes and fears for the future in rural China. (February 2018) - Zhao, Jingxin; Sun, Ping; Wang, Meifang; Zhang, Wenxin
Abstract: The present study examined the contents of future hopes and fears among Chinese adolescents left behind by one or both of their rural-to-urban migrant parents compared to those from rural and urban nonmigrant families. Data from 1083 participants (50.2% boys; Mage  = 13.50 years; SD = 1.06) indicated that adolescents reported future hopes and fears in a variety of life domains, including future education, academics, occupation, marriage and family, parents' and relatives' wellbeing, interpersonal relationships, leisure activities, wealth and self-related issues. Adolescents from both-parent-migrant families reported more hopes and fears for interpersonal relationships and more fears for parents' and relatives' wellbeing than other adolescents. Moreover, boys from migrant families reported more hopes for occupation and fewer hopes for interpersonal relationships than girls from migrant families, whereas no gender differences were found among adolescents from nonmigrant families. These results suggest the important roles of parental migration in adolescents' future thinking.